Efficacy and Safety of First-Line Treatment Strategies for Anaplastic Lymphoma Kinase-Positive Non-Small Cell Lung Cancer: A Bayesian Network Meta-Analysis - Peng, Ling; Lu, Dafeng; Xia, Yang; Hong, Shaodong; Selvaggi, Giovanni; Stebbing, Justin; Sun, Yilan; Liang, Fei (Frontiers in Oncology, 2021)
Background: Targeted therapies have led to significant improvement in the management and prognosis of anaplastic lymphoma kinase (ALK) positive non-small cell lung cancer (NSCLC). We performed a network meta-analysis of frontline treatment options of ALK-positive NSCLC to provide clinical guidance. Methods: PubMed, Embase, ClinicalTrials.gov, and international conference databases were searched to identify relevant trials from inception to 30 June 2021. Phase III randomised controlled trials comparing treatments for patients with ALK-positive advanced NSCLC in the first line setting were included in a Bayesian network meta-analysis. Eligible studies reported at least one of the following clinical outcomes: progression free survival (PFS), overall survival (OS), risk of central nervous system (CNS) progression, adverse events of grade (G) 3 or higher (G3 AEs), or serious adverse events (SAEs). Hazard ratios (HR) and confidence interval (CI) for primary outcome of PFS and secondary outcome of OS and risk of central nervous system (CNS) progression were obtained. A multivariate, consistency model, fixed-effects analysis was used in the network meta-analysis. Data on G3 AEs and SAEs were abstracted and meta-analyzed. Risk for bias (RoB) was assessed using the Cochrane Collaboration’s tool. Results: Nine RCTs comprising 2484 patients were included with seven treatments: alectinib, brigatinib, ceritinib, crizotinib, ensartinib, lorlatinib and chemotherapy. Compared with chemotherapy, ALK-tyrosine kinase inhibitors (TKIs) significantly prolong PFS and reduced risk of CNS progression except for ceritinib. Lorlatinib appears superior at reducing risk of CNS progression. None of the ALK-TKIs have a significantly prolonged OS compared with chemotherapy. Lorlatinib increases the risk of G3 AEs compared with alectinib (odds ratio 4.26 [95% CrI 1.22 to 15.53]), while alectinib caused the fewest G3 AEs. Conclusions: Lorlatinib is associated with the highest PFS benefit and lowest risk of CNS progression benefits for patients with advanced ALK-positive NSCLC, compared with other first line treatments but with higher toxicity. The implementation of newer generation of ALK-TKIs in the first line treatment of ALK-positive NSCLC into current clinical practice is evolving rapidly.